2003
DOI: 10.1046/j.1440-1746.2003.02936.x
|View full text |Cite
|
Sign up to set email alerts
|

Longer survival in female than male with hepatocellular carcinoma

Abstract: The survival of female cases of HCC was longer than that of male cases. Disparities in the type of follow-up for women in comparison to men exist and may contribute to gender disparities in survival. Women with a high risk for HCC tended to be better cared for during the follow-up. To reduce gender disparities in survival, efforts should be directed at the earlier identification of HCC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
47
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 53 publications
(56 citation statements)
references
References 24 publications
9
47
0
Order By: Relevance
“…According to previous research that implied the cause of the sex difference in survival with HCC, women were more closely followed-up compared to men in the detection of early-stage HCC among high-risk patients (19). Our study also revealed that males were less likely to receive regular hepatologist visits.…”
Section: Discussionsupporting
confidence: 54%
See 2 more Smart Citations
“…According to previous research that implied the cause of the sex difference in survival with HCC, women were more closely followed-up compared to men in the detection of early-stage HCC among high-risk patients (19). Our study also revealed that males were less likely to receive regular hepatologist visits.…”
Section: Discussionsupporting
confidence: 54%
“…Non-viral cause n=6 (5) Group B (regular visits to other divisions) n=41 (19) Group C (no hospital visits) n=12 (8) Figure 2). …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Many reports from several countries of different continents showed that the male gender was obviously predominant in the distribution of HCC in the individuals [2][3][4]. Besides, some published papers found better postoperative survival in female HCC patients than in males [13][14][15]. The reason that might account for our different results should be further studied.…”
Section: Discussionmentioning
confidence: 81%
“…First, HCC mainly occurs in males (with a male/female ratio between 5 and 9 1 ), with a poorer outcome in males than in females. 7 Second, occurrence of HCC has been reported in patients treated with androgens 8 or in bodybuilders. 9 Third, serum testosterone has been found to be a predictive factor of HCC occurrence in patients with hepatitis C virus and cirrhosis 10 and in hepatitis B virus carriers.…”
mentioning
confidence: 99%